Lifestyle and neurocognition in older adults with cognitive impairments: A randomized trial - Blumenthal, James A. (Neurology, 2019)
OBJECTIVE: To determine the independent and additive effects of aerobic exercise (AE) and the Dietary Approaches to Stop Hypertension (DASH) diet on executive functioning in adults with cognitive impairments with no dementia (CIND) and risk factors for cardiovascular disease (CVD). METHODS: A 2-by-2 factorial (exercise/no exercise and DASH diet/no DASH diet) randomized clinical trial was conducted in 160 sedentary men and women (age >55 years) with CIND and CVD risk factors. Participants were randomly assigned to 6 months of AE, DASH diet nutritional counseling, a combination of both AE and DASH, or health education (HE). The primary endpoint was a prespecified composite measure of executive function; secondary outcomes included measures of language/verbal fluency, memory, and ratings on the modified Clinical Dementia Rating Scale. RESULTS: Participants who engaged in AE (d = 0.32, p = 0.046) but not those who consumed the DASH diet (d = 0.30, p = 0.059) demonstrated significant improvements in the executive function domain. The largest improvements were observed for participants randomized to the combined AE and DASH diet group (d = 0.40, p = 0.012) compared to those receiving HE. Greater aerobic fitness (b = 2.3, p = 0.049), reduced CVD risk (b = 2.6, p = 0.042), and reduced sodium intake (b = 0.18, p = 0.024) were associated with improvements in executive function. There were no significant improvements in the memory or language/verbal fluency domains. CONCLUSIONS: These preliminary findings show that AE promotes improved executive functioning in adults at risk for cognitive decline. CLINICALTRIALS.GOV IDENTIFIER: NCT01573546. CLASSIFICATION OF EVIDENCE: This study provides Class I evidence that for adults with CIND, AE but not the DASH diet significantly improves executive functioning.